Teachers' Emotional Management and Stress Coping: Gender Perspectives and Their Impact on Psychological Well-being - Ema Yudiani; Jesyia Meyrinda (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
This study investigated the effect of gender on emotional management, coping styles, and psychological well-being among 110 senior high school teachers in Palembang, Indonesia. Using a quantitative research design, data were collected through the Psychological Well-Being Scale, Self-Efficacy Scale, and Coping Style Questionnaire. Data analysis involved independent sample t-tests, Pearson correlations, and moderated regression. The findings revealed significant gender differences in emotional coping strategies and aspects of psychological well-being. Specifically, female teachers exhibited higher self-efficacy and tended to use emotion-oriented coping more frequently, while male teachers showed higher levels of problem-focused coping, self-acceptance, and autonomy. Crucially, gender significantly moderated the relationship between emotional coping and psychological well-being, indicating a distinct impact on how coping mechanisms influence well-being based on gender. Emotion-oriented coping was more strongly associated with psychological well-being for female teachers, whereas problem-oriented coping showed a more pronounced positive correlation for male teachers. This research highlights the critical need for gender-sensitive approaches in developing interventions aimed at optimizing teacher well-being and, consequently, enhancing educational quality. The findings provide useful direction for developing psychological support programs that take these gender differences into account. This can help build a stronger and more effective group of teachers.